A case exploration of the critical success factors of innovation labs: implications for the UAE - ALBLOOSHI, AMAL (2017)
The dissertation study was conducted to arrive at in-depth understanding of the concept of innovation in general and innovation labs specifically, the different challenges that face innovation labs and the factors that lead to successful delivery of innovations. The dissertation aims at improving the level of performance of the newly set innovation labs in the United Arab Emirates. This can be achieved through the understanding of the key elements that enable innovation labs to successfully deliver innovations in UAE organizations. Considering the need to investigate and analyse existing innovation labs within UAE, a case study following qualitative approach was selected for this dissertation. The research findings revealed the importance of innovation and the significant role innovation labs play to support organizational growth strategy. The research discovered several challenges that face innovation labs in UAE, such as people’s mind-set and resistance to accept change and financial limitations. The proposed factors that lead to successful delivery of innovations are diffusion of innovation, adoption of open innovation, flexible strategy and well-defined processes. Overall the study was able to make contribution to the existing literature by providing the essentials for innovation labs in UAE that help to increase their effectiveness and enable them to deliver successful innovations.